Distinct conformations of GPCR–β-arrestin complexes mediate desensitization, signaling, and endocytosis - Cahill, Thomas J. (Proc Natl Acad Sci U S A, 2017)
β-Arrestins (βarrs) interact with G protein-coupled receptors (GPCRs) to desensitize G protein signaling, to initiate signaling on their own, and to mediate receptor endocytosis. Prior structural studies have revealed two unique conformations of GPCR–βarr complexes: the “tail” conformation, with βarr primarily coupled to the phosphorylated GPCR C-terminal tail, and the “core” conformation, where, in addition to the phosphorylated C-terminal tail, βarr is further engaged with the receptor transmembrane core. However, the relationship of these distinct conformations to the various functions of βarrs is unknown. Here, we created a mutant form of βarr lacking the “finger-loop” region, which is unable to form the core conformation but retains the ability to form the tail conformation. We find that the tail conformation preserves the ability to mediate receptor internalization and βarr signaling but not desensitization of G protein signaling. Thus, the two GPCR–βarr conformations can carry out distinct functions.